ECONOMIC POSITION OF AGRICULTURAL ENTERPRISES IN VOJVODINA (2001-2009) - Vеljko Vukoje; Vladislav Zekić (Ekonomika Poljoprivrede (1979), 2010)
The paper analyses the main indicators of financial position of agricultural enterprises in Vojvodina for the period 2001-2009. Due to the length of the observed period, considerable devaluation of RSD (60.6%) and high inflation rate (125.7%), all the values are expressed in euros.